1988
DOI: 10.1073/pnas.85.9.3044
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of human breast cancer: evidence for autosomal dominant transmission in high-risk families.

Abstract: Segregation analysis of breast cancer in families can provide the logical basis and the specific genetic models for mapping and identifying genes responsible for human breast cancer. Patterns of breast cancer occurrence in families were investigated by complex segregation analysis. In a sample of 1579 nuclear families ascertained through a populationbased series of probands, an autosomal dominant model with a highly penetrant susceptibility allele fully explained disease clustering. From the maximum-likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
199
2
4

Year Published

1990
1990
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(209 citation statements)
references
References 27 publications
4
199
2
4
Order By: Relevance
“…Testicular cancer patients may be less likely to know of cancers in the grandparents than in their first-degree relatives. On the other hand, it may be that there is a deficit of factors predisposing to common (Kaldor et al, 1987;Fossa et al, 1990;Moller H. et al, 1993;Jacobsen et al, 1993;van-Leeuwen et al, 1993 (Newman et al, 1988;Claus et al, 1991;Iselius et al, 1991Iselius et al, , 1992. If we set the gene frequency to 1:200-1:300, the expected number of breast(-ovarian) families would be 3-5.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular cancer patients may be less likely to know of cancers in the grandparents than in their first-degree relatives. On the other hand, it may be that there is a deficit of factors predisposing to common (Kaldor et al, 1987;Fossa et al, 1990;Moller H. et al, 1993;Jacobsen et al, 1993;van-Leeuwen et al, 1993 (Newman et al, 1988;Claus et al, 1991;Iselius et al, 1991Iselius et al, , 1992. If we set the gene frequency to 1:200-1:300, the expected number of breast(-ovarian) families would be 3-5.…”
Section: Discussionmentioning
confidence: 99%
“…Late age at first pregnancy (>30 years) is known to be associated with increased breast cancer risk [Kelsey, 1979] and may have either nongenetic or genetic origins (e.g., genetic syndromes involving infertility). Several investigators have demonstrated that susceptibility to breast cancer is increased in some families by an autosomal dominant gene [Newman et al, 1988;Williams and Anderson, 1984;Go et al, 1983], but the genetic form of the disease appears to affect only a minority of patients (approximately 4%) [Newman et al, 1988]. Some women, even in high-risk families, appear to inherit susceptibility from their mothers and transmit it to their daughters without ever becoming affected themselves.…”
Section: Modelsmentioning
confidence: 99%
“…Approximately, five to ten percent of all breast and ovarian cancers are due to genetic predisposition with autosomal dominant transmission (Newman et al, 1988;Claus et al, 1991;Schildkraut et al, 1989). Two major breast and ovarian cancer susceptibility genes, BRCA1 (MIM# 113705) and BRCA2 (MIM# 600185), have been identified (Miki et al, 1994;Wooster et al, 1995;Tavtigian et al, 1996).…”
Section: Introductionmentioning
confidence: 99%